Fabrication and properties of luminescence polymer composites with erbium/ytterbium oxides and gold nanoparticles - Burunkova, Julia A.; Denisiuk, Ihor Yu.; Zhuk, Dmitri I.; Daroczi, Lajos; Csik, Attila; Csarnovics, István; Kokenyesi, Sándor (Beilstein Journal of Nanotechnology, 2016)
Rare-earth-doped optical materials are important for light sources in optoelectronics, as well as for efficient optical amplification elements and other elements of photonics. On the basis of the previously developed method of anhydrous, low-temperature synthesis of Er/Yb oxides from their chlorides we fabricated proper nanoparticles with defined parameters and used them for the development of optically transparent, luminescent polymer nanocomposite with low optical scattering, suitable for direct, light-induced formation of photonic elements. Introduction of preformed gold nanoparticles in such a nanocomposite was also performed and an enhancement of luminescence due to the influence of plasmon effects was detected.
Keywords: gold nanoparticles; luminescence; optical materials; polymer nanocomposites; rare-earth oxide nanoparticles